The NoXi database: multimodal recordings of mediated novice-expert interactions - Cafaro, Angelo; Wagner, Johannes; Baur, Tobias; Dermouche, Soumia; Torres, Mercedes Torres; Pelachaud, Catherine; André, Elisabeth; Valstar, Michel F. (2017)
We present a novel multi-lingual database of natural dyadic novice-expert interactions, named NoXi, featuring screen-mediated dyadic human interactions in the context of information exchange and retrieval. NoXi is designed to provide spontaneous interactions with emphasis on adaptive behaviors and unexpected situations (e.g. conversational interruptions). A rich set of audio-visual data, as well as continuous and discrete annotations are publicly available through a web interface. Descriptors include low level social signals (e.g. gestures, smiles), functional descriptors (e.g. turn-taking, dialogue acts) and interaction descriptors (e.g. engagement, interest, and fluidity).